It’s a Miracle They’re Still Talking! The Saga of the GRP-MILF Peace Talks - R. Rodil, B. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
During the fifteen months of peace negotiations from January 1997, the Government of the Republic of the Philippines (GRP) and the Moro Islamic Liberation Front (MILF) had its agreements and disagreements. The agreements were threefold: January 27, 1997, initial accord on a six-point temporary truce appli cable only in Buldon, Maguindanao. September 12, 1997, agreenent on the ground rules of the general cessation of hostilities. On November 14, 1997, the signing of the cease-fire agreement that,among other things, classifies kidnapping, summary executions, ambushes and bombings as "provocative and hostile acts.’ The disagreements are armed encounters that punctuated the periods between the agreements. The peace negotiation is still holding. It is indeed miracle that they are still talking. As of this writing, they have yet to agree on the main agenda for the talks.